Políticas públicas e a agricultura familiar no assentamento - Reis, Saulo Ferreira (2015)
This research investigates public policy and family farming in the Serra Dourada settlement, located in the city of Goiás, Goiás. It analyzes the design and operation of the National Family Farming Strengthening Program (PRONAF), the Program for Food Acquisition (PAA) and the National School Feeding Programme (PNAE) and the degree of integration in the state of Goiás and the Serra Dourada settlement, noting how are given the productive integration mechanisms and their relationship with the market. Assuming that public policy is state action aimed at the carrier citizen rights, we will outline the role, responsibility and state action, the market and families facing farmers for establishing and implementing public policies. Thus, it is normally analysis of the subject from the paradigm of agrarian capitalism, the agrarian question and the applicable legislation on family agriculture, with one seated interviewed on field research. Also analyzing public policies Technical Assistance, Health and Infrastructure, which interface with the PRONAF, PAA and PNAE, and can directly influence the development and access of these policies. It concludes that the productive insertion mechanisms of family farms seem to show incomplete or inefficient because it does not account for the entire production process. The precariousness of ATER service and the absence of clear policies of federal, state and municipal spheres, specific to the reality of family farming, which allow different treatment according to their characteristics and their production scale. Although many producing and marketing a lot, this did not change the way you organize socially and did not interfere in the way of relating to the land. The relationship with the formal or informal market takes place as a matter of convenience and opportunity, which shows that current legislation is incompatible with the subject of such policies, in which the low adhesion public policies to show an inconsistency between this ideal and the Subject real, it does not consider all the characteristics of this social group, such as social and economic aspects, factors which may concern the membership or not this logic as it develops the production and falls in the market.